Teaching Grammar in Higher Education - Siti Aisyiyah (Politeknik Negeri Jember, 2019)
Grammar is considered as a complicated subject for most English learners. This makes the learners are not interested in learning grammar. Moreover, many teachers usually tolerate the learnersâ€™ weakness in grammar. Grammar has been a controversial topic for years; nevertheless, learnersâ€™ grammar acquisition and awareness can improve the quality of their English skill. To have good acquisition and awareness in grammar, the learners need a long and continuous process. Therefore, the learners are required to have autonomy in learning grammar. Learner autonomy refers to learners responsibility to their own learning process. Some experts define learner autonomy as â€œthe ability to take charge of oneâ€™s own learningâ€, and â€œplaying an active role in learningâ€. This paper reports on how to foster learner autonomy in grammar class by combining learner-centered grammar teaching and explicit grammar teaching. Learner-centered grammar teaching refers to inductive approach, while explicit grammar teaching deals with deductive approach. Learner-centered grammar teaching was carried out through group discussion, presentation and language awareness activities. Meanwhile, explicit grammar teaching was done to review the learnersâ€™ materials in presentation and reinforce their acquisition. Those two different approaches were applied due to differences on learnerâ€™s characteristics and needs. Result showed some success in the practice of autonomy, indicated by changes on learnersâ€™ attitude. However, many learners showed that they focused more on obtaining score than on developing their language acquisition. By implementing the approach, the teacher can assist learners to be aware of their ability to learn independently and equip them with the skill needed for long-life learning.